Research and study paths: Indicators of the development of the dialectics Rutas de investigación y estudio: indicadores del desarrollo de la dialéctica - Parra, Verónica; Otero, Maria Rita (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract In this work, we describe a set of didactic - mathematical indicators to determine the development of the dialectics. These indicators are not definitive and their first formulations are the result of the analysis of the data obtained when implementing a research and study paths (RSP) at the last year of the Argentine secondary level. From these indicators, we conclude that the most frequent dialectics are: individual and collective, subject and out-of-subject, research and study, praxeological analysis-synthesis/didactic synthesis-analysis and black boxes and clear boxes. Keywords: Research and study paths, praxeological analysis-synthesis, ATD. Resumen En este trabajo describimos un conjunto de indicadores didáctico-matemáticos para determinar el desarrollo de las dialécticas. Estos indicadores no son definitivos y sus primeras formulaciones son producto del análisis de los datos obtenidos al implementar un recorrido de estudio e investigación (REI) en el último año del nivel secundario argentino. A partir de estos indicadores, concluimos que las dialécticas más frecuentes son: individuo y del colectivo, tema y fuera-de-tema, estudio e investigación, análisis-síntesis praxeológica/análisis-síntesis didáctica y cajas negras y cajas claras.